MiR‐548d‐3p/TP53BP2 axis regulates the proliferation and apoptosis of breast cancer cells. (13th December 2015) - Song, Qiong; Song, Jiangqiang; Wang, Qimin; Ma, Yanling; Sun, Nai; Ma, Jieyu; Chen, Qiu; Xia, Guishan; Huo, Yanping; Yang, Longqiu; Li, Baolin
Abstract : High‐level copy number of miR‐548d‐3p is critically involved in the low survival ratio. miR‐548d‐3p plays an important role on regulating the proliferation and apoptosis of breast cancer. Abstract: Fast growth and hardly any apoptosis are important characteristics of breast cancer, which assure the spread via invasion and metastasis of breast cancer cells. Inhibition of fast proliferation and induction of apoptosis are critical way to cure this cancer. microRNAs (miRNAs) had been increasingly reported to be the critical regulator of tumorigenesis. In our study, we found that increasing copy number of miR‐548d‐2‐3p is critically involved poor prognosis. We overexpressed miR‐548d‐3p in MDA‐MB‐231cells and found that the proliferation was promoted significantly, whereas the inhibition of miR‐548d‐3p repressed the proliferation of MDA‐MB‐231 cells and also induced the increase in apoptosis. Additionally, we found that miR‐548d‐3p downregulated the expression of TP53BP2 by directly targeting the 3′UTR. We also found that knockdown of TP53BP2 significantly resorted the proliferation and apoptosis regulated by miR‐548d‐3p inhibitor. Our study showed that miR‐548d‐3p/TP53BP2 pathway is critically involved in the proliferation and apoptosis of breast cancer cells and may be new therapeutic target of breast cancer cells.